The Effect of Company Size, Profitability and Company Age on Environmental Performance with Environmental Costs as a Moderating Variable - Ignasius G. K. Panggabean; Yohanes Kevin Lukna; Putri Balqis; Rara Suganda; Willy Febrian Sipayung; Vina Arnita (Journal of Indonesian Management, 2025)
The objective of this study is to examine the impact of company size, profitability, and company age on environmental performance, with environmental costs acting as a moderating variable. The study's population consists of companies within the energy and healthcare sectors, from which a sample of 12 companies was selected for the period spanning from 2021 to 2023, following purposive sampling methodology. To analyze the data, moderation regression techniques were applied using the SPSS software, allowing for an evaluation of the direct effects of each independent variable as well as the moderating effects on these relationships. The findings revealed that company size does not exert a significant influence on environmental performance, and similarly, profitability does not have a substantial effect on environmental performance. However, company age was found to have a noteworthy and significant impact on environmental performance. Regarding the moderating effect of environmental costs, the study indicated that environmental costs positively strengthen the relationship between profitability and environmental performance, while they serve to weaken the relationship between company age and environmental performance. Additionally, environmental costs were not found to moderate the effect of company size on environmental performance.